Multi-Objective Optimization of Ship Design for the Effect of Wind Propulsion - Timoleon Plessas; Apostolos Papanikolaou (Journal of Marine Science and Engineering)
International regulations and market demand for zero-emission transportation are accelerating the adoption of sustainable solutions in the shipping industry. Wind-Assisted Propulsion Systems (WAPSs) present a promising alternative, as elaborated on in the EU-funded Orcelle Wind project. This paper deals with the integration of wing sails into the conceptual design of a Very Large Crude Carrier (VLCC) using a parametric, multi-objective optimization framework. The results reveal that optimized VLCC designs with WAPSs can achieve over 20% reductions in fuel consumption and greenhouse gas emissions compared to conventional designs. Additionally, the obtained optimized designs exhibit notable differences in the main design characteristics and hull form compared to conventional designs, highlighting the importance of multi-objective optimization in the early design stage to tap the potential of WAPS technologies and wind propulsion.